2015
DOI: 10.1097/iae.0000000000000354
|View full text |Cite
|
Sign up to set email alerts
|

Subfoveal Choroidal Thickness in Idiopathic Choroidal Neovascularization and Treatment Outcomes After Intravitreal Bevacizumab Therapy

Abstract: Subfoveal choroidal thickness is reduced and may be associated with the pathophysiology of idiopathic CNV. Intravitreal bevacizumab resulted in significant visual and anatomical improvement in patients with idiopathic CNV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Choroidal thickness changes have been described in age-related choroidal atrophy, 2 pachychoroid spectrum conditions like central serous chorioretinopathy, 3,4 and choroidal inflammatory diseases including Vogt-Koyanagi-Harada syndrome. 57 Choroidal thinning has also been implicated in age-related macular degeneration, 811 diabetic retinopathy, 12,13 retinal vein occlusions, 14,15 and as a consequence of anti-vascular endothelial growth factor (anti-VEGF) therapy. 1619 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choroidal thickness changes have been described in age-related choroidal atrophy, 2 pachychoroid spectrum conditions like central serous chorioretinopathy, 3,4 and choroidal inflammatory diseases including Vogt-Koyanagi-Harada syndrome. 57 Choroidal thinning has also been implicated in age-related macular degeneration, 811 diabetic retinopathy, 12,13 retinal vein occlusions, 14,15 and as a consequence of anti-vascular endothelial growth factor (anti-VEGF) therapy. 1619 …”
Section: Introductionmentioning
confidence: 99%
“…2024 Much of the difficulty in achieving reliable choroidal thickness measurements is due to the variable and often obscure appearance of the choroidal-scleral junction (CSJ) that determines the posterior boundary of the choroid. While some studies appear to use the border of the choroidal vascular lumen as the posterior boundary, 15,2528 others defined the border of the choroid stroma or sclera as the CSJ. 2932 In some individuals, there is also a hyporeflective band corresponding to the suprachoroidal layer, which may further contribute to variability in choroidal thickness measurements.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although several studies have shown changes in the subfoveal choroidal thickness (SFCT) after administration of intravitreal anti-vascular endothelial growth factor (VEGF) in patients with neovascular AMD, [4][5][6][7] other studies have not found any changes. [8][9][10] To our knowledge, no previous studies have investigated these changes in patients with PNV.…”
mentioning
confidence: 99%
“…Idiopathic choroidal neovascularization (ICNV) is defined as CNV occurring in patients younger than 50 years with no detectable primary ocular or systemic diseases, such as pathologic myopia (PM), angioid streak, trauma, or other inflammatory or hereditary disorders [1,2] . Although the natural progression and the visual prognosis of ICNV are more favorable than for CNV attributable to agerelated macular degeneration (AMD), and majorities of patients with ICNV have good response to antivascular endothelial growth factor (VEGF) therapy, some of these patients nonetheless have persistent CNV, and even decreased vision, and need repeated anti-VEGF therapy [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Central retinal thickness (CRT, thickness of the 1-mm central retina) was measured by OCT; lesion area was measured on fluorescein angiograms as described previously [18] . Our exclusion criteria are as follows: (1) clinical features suggesting that CNV was secondary to other causes such as AMD, PM, trauma, choroiditis, or hereditary diseases in the studied or contralateral eye; (2) axial length >26.0 mm or myopia> -6 diopter; (3) prior local or systemic treatment for ICNV, or previous intraocular surgery; (4) systemic inflammatory diseases such as autoimmune disease, diabetes mellitus or malignoma.…”
Section: Introductionmentioning
confidence: 99%